2010
DOI: 10.1016/j.ijdevneu.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal IV nicotine exposure produces a sex difference in sensorimotor gating of the auditory startle reflex in adult rats

Abstract: Maternal smoking during pregnancy is associated with auditory processing deficits in children; these effects have been confirmed with animal models of continuous high-dose prenatal nicotine exposure. The present experiments utilized a novel, low-dose, intermittent, intravenous (IV) gestational nicotine exposure model to investigate potential deficits on the preattentive process of sensorimotor gating, as indexed by prepulse inhibition (PPI), in preweanling and adult rat offspring. Pregnant dams received bolus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 93 publications
5
20
2
Order By: Relevance
“…These data are consistent with previous results from our laboratory, which indicate enduring behavioral and/or neurophysiological consequences of IV PN exposure (Harrod et al, 2012, 2011; Lacy et al, 2012, 2011; Morgan et al, 2013). Furthermore, these data support a small, but growing literature showing that PN exposure alters motivated behavior in offspring; particularly in regard to drug self-administration (Buka et al, 2003; Franke et al, 2008; Kandel et al, 1994; Levin et al, 2006; Weissman et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data are consistent with previous results from our laboratory, which indicate enduring behavioral and/or neurophysiological consequences of IV PN exposure (Harrod et al, 2012, 2011; Lacy et al, 2012, 2011; Morgan et al, 2013). Furthermore, these data support a small, but growing literature showing that PN exposure alters motivated behavior in offspring; particularly in regard to drug self-administration (Buka et al, 2003; Franke et al, 2008; Kandel et al, 1994; Levin et al, 2006; Weissman et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Overall, less nicotine is needed to produce behavioral alterations in offspring, relative to other exposure models. The intentional administration of low overall concentrations of daily nicotine allows the experimenter to observe potential neurodevelopmental/neurobehavioral alterations in offspring without producing differences in litter composition, low birth weight, or any of the behavioral milestones tested, relative to PS controls (Harrod et al, 2012, 2011; Lacy et al, 2012, 2011; Morgan et al, 2013). Practically, this issue is important because it suggests that the modulation of METH reinforcement in PN-exposed offspring in the present study is due to PN-mediated alterations of neural development, rather than nicotine-induced changes in birth weight, and hence, growth anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory uses a model of intravenous (IV) PN exposure in rats to mimic the pharmacokinetic profile of nicotine absorption with tobacco smoke inhalation [20,21]. Several studies from our laboratory have shown that 3×/day IV nicotine administration produces significant and long-lasting neurobehavioral alterations in exposed offspring [17,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies from our laboratory have shown that 3×/day IV nicotine administration produces significant and long-lasting neurobehavioral alterations in exposed offspring [17,21,22]. In the present study, we used adult male and female offspring exposed to IV PN or prenatal saline (PS) and assessed methamphetamine (METH)-induced hyperactivity and METH-induced sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…The present experiments utilized a low-dose IV PN exposure method that has been shown to alter the expression of brain-derived neurotrophic factor in offspring (Harrod et al, 2011), and to produce alterations in various behavioral assays including prepulse inhibition of the acoustic startle response (Lacy et al, 2011), sucrose-maintained responding (Lacy et al, 2012), and methamphetamine self-administration (Harrod et al, 2012). We determined if PN exposure altered the expression of orexin in the LH and in its projections to the VTA using immunohistochemical techniques in tissue from adult offspring (~130 days) that were prenatally exposed to nicotine or saline.…”
Section: Introductionmentioning
confidence: 99%